Struggling Readers? Using Theory to Complicate Understandings of What It Means to Be Literate in School. (November 2015) - Frankel, Katherine K.; Jaeger, Elizabeth L.; Brooks, Maneka Deanna; Randel, Maryl A.
Theories guide many aspects of literacy research. In this article we describe four theoretical approaches that we have used in qualitative research with students who are perceived to struggle with reading in school, including: New Literacy Studies, Disability Studies in Education, Bioecological Systems Theory, and Cultural Historical Activity Theory. We provide a brief overview of each of the theories and then explain how we have used them to gain insights about students with whom we have worked in the context of our research. Although grounded in distinct perspectives, we argue that each of the theories are lenses through which we were better able to understand the complexities of students' struggles with reading. We further argue that the theories are united in their ability to broaden the perspectives of researchers and teachers to better account for the social, cultural, and institutional factors that shape literacy teaching and learning in schools. We conclude by questioning the use of the term "struggling reader" and highlighting the implications of our individual theoretical frames and analyses for both research and practice.